Theoretical Design of Biodegradable Phthalic Acid Ester Derivatives in Marine and Freshwater Environments. Issue 10 (19th October 2020) - Zhang, Haigang; Zhao, Chengji; Na, Hui
Abstract: The biodegradability of phtalic acid esters in marine and freshwater environments was characterized by their binding free energy with corresponding degrading enzymes. According to comprehensive biodegradation effects weights, the binding free energy values were converted into dimensionless efficacy coefficient using ratio normalization method. Then, considering comprehensive dual biodegradation effects value and the structural parameters of PAEs in both marine and freshwater environments, a 3D‐QSAR pharmacophore model was constructed, five PAE derivatives (DBP−COOH, DBP−CHO, DBP−OH, DINP−NH2, and DINP−NO2 ) were screened out based on their environmental friendliness, functionality and stability. The prediction of biodegradation effects on five PAE derivatives by biodegradation models in marine and freshwater environment increased by 15.90 %, 15.84 %, 27.21 %, 12.33 %, and 8.32 %, and 21.57 %, 15.21 %, 20.99 %, 15.10 %, and 9.74 %, respectively. By simulating the photodegradation path of the PAE derivative molecular, it was found that DBP−OH can generate . OH and provides free radicals for the photodegradation of microplastics in the environment. Abstract : Phtalic acid esters, as the main additive component of microplastics, are hard‐to‐degrade. This study developed a ratio‐normalization‐based 3D‐QSAR comprehensive model for designing environmental friendly PAE derivatives. The proposed method has advantages in reflecting dual biodegradation effects of PAEs in marine and freshwater environments. The PAE derivative DBP‐OH can form OH and promote the photodegradation of microplastics under natural light.